Design and Implementation of Siprakfis (Physics Laboratory Practical Management Information System) to Optimize Practical Services in Higher Education - Widyastuti, Widyastuti; Rofiudin, Muhammad; Rohim, Ahmad Minanur (Physics Education Research Journal, 2024)
Physics laboratories often face difficulties managing practicums, especially in scheduling, equipment tracking, assessment, and evaluation of practicum results. The mismatch between practicum needs and resource availability usually results in delays, administrative errors, and increased workload of laboratory staff. This study proposes the development of a Physics Laboratory Practicum Management Information System (SIPRAKFIS) to optimize practicum management in physics laboratories. The research method used is R&D with a waterfall development model, which includes communication, planning, modeling, construction, and deployment stages. SIPRAKFIS was developed using the PHP MySQL programming language. System testing was done through unit testing, functionality, usability, and implementation. The study results indicate that SIPRAKFIS is feasible to use in practicum management and can be accessed online via www.labfisikauin.com. Unit testing on the login system was declared victorious. Functional testing obtained good results, namely a functional value of 1. Usability testing obtained a value of 82.59%. Deployment testing showed that the system can be run on various browsers, namely Mozilla Firefox, Google Chrome, and Internet Explorer. SIPRAKFIS can help facilitate the management of practicum services, reduce administrative errors, speed up the practicum scheduling process, and facilitate equipment monitoring and reporting of practicum values. The results of this study can also be further developed for research and testing services.